![\frac{x^2+3x+2}{6+3x} = \frac{(x+2)(x+1)}{6+3x} \frac{x^2+3x+2}{6+3x} = \frac{(x+2)(x+1)}{6+3x}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2%2B3x%2B2%7D%7B6%2B3x%7D%20%3D%20%5Cfrac%7B%28x%2B2%29%28x%2B1%29%7D%7B6%2B3x%7D)
Решим дискриминант:
x^2+3x+2 = 0
D = b²-4ac => 3²-4*1*2 = 9-8 = 1>0, 2 корня.
x = ![\frac{-b+-\sqrt{D} }{2a} \frac{-b+-\sqrt{D} }{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%2B-%5Csqrt%7BD%7D%20%7D%7B2a%7D)
x₁ = ![\frac{-3+1}{2} = -1 \frac{-3+1}{2} = -1](https://tex.z-dn.net/?f=%5Cfrac%7B-3%2B1%7D%7B2%7D%20%3D%20-1)
x₂ = ![\frac{-3-1}{2} = -2 \frac{-3-1}{2} = -2](https://tex.z-dn.net/?f=%5Cfrac%7B-3-1%7D%7B2%7D%20%3D%20-2)
Получается: (x-2)(x-1).
Есть итого три точки для координатной прямой: x₁ = -2, x₂ = -1, x₃ = 6+3x = 3x = -6 => -6/3 = -2
Ответ: 2 точки, знака неравенства нет, поэтому только этот ответ.